Role of endothelial cell apoptosis in regulation of skeletal muscle angiogenesis during high and low salt intake - de Resende, M. M.; Amaral, S. L.; Munzenmaier, D. H.; Greene, A. S. (Amer Physiological Soc, 2006)
Angiogenesis, under normal conditions, is a tightly regulated balance between pro- and antiangiogenic factors. The goal of this study was to investigate the mechanisms involved in the control of the skeletal muscle angiogenic response induced by electrical stimulation during the suppression of plasma renin activity (PRA) with a high-salt diet. Rats fed 0.4% or 4% salt diets were exposed to electrical stimulation for 7 days. The tibialis anterior ( TA) muscles from stimulated and unstimulated hindlimbs were removed and prepared for gene expression analysis, CD31-terminal deoxynucleotide transferase-mediated dUTP nick-end labeling ( TUNEL) double-staining assay, and Bcl-2 and Bax protein expression by Western blot. Rats fed a low-salt diet showed a dramatic angiogenesis response in the stimulated limb compared with the unstimulated limb. This angiogenesis response was significantly attenuated when rats were placed on a high-salt diet. Microarray analysis showed that in the stimulated limb of rats fed a low-salt diet many genes related to angiogenesis were upregulated. In contrast, in rats fed a high-salt diet most of the genes upregulated in the stimulated limb function in apoptosis and cell cycle arrest. Endothelial cell apoptosis, as analyzed by CD31-TUNEL staining, increased by fourfold in the stimulated limb compared with the unstimulated limb. There was also a 48% decrease in the Bcl-2-to-Bax ratio in stimulated compared with unstimulated limbs of rats fed a high-salt diet, confirming severe apoptosis. This study suggests that the increase in endothelial cell apoptosis in TA muscle might contribute to the attenuation of angiogenesis response observed in rats fed a high-salt diet.
Keywords: Bax; Bcl-2; gene expression